Environmental characteristics of clay and claybased minerals - Aboudi Mana, Suzanne Christine; Mohd Hanafiah, Marlia; Chowdhury, Ahmed Jalal Khan (Taylor and Francis Online, 2017)
Clay is an inherently occurring material constituted with fined-grained mineral. The minerals are generally less than 2 microns and occur to be plastic in water content which solidify when dried. In the earth surface, clay represents the most available mineral and forms rocks known as shale and is the major component of sedimentary rocks. The small size of the particles and their unique crystal structures give clay materials special properties. These properties include: cation exchange capabilities, plastic behaviour when wet, catalytic abilities, swelling behaviour,and low permeability. They give to clay and clay-based minerals higher application in many industries and processes. To acknowledge all the features of clay and clay-based minerals, the understanding of their properties especially the cation exchange capability which affects the mechanical and physical properties of the clay is important, and also to acquire information about the crystal structure of clay mineral in general and montmorillonite especially. The purpose of this laboratory is to illustrate the importance of chemistry on the physical properties of montmorillonite, the clay mineral most often used to isolate dangerous waste materials from the environment.